Dinâmica de um qubit interagindo com ambientes térmicos via modelos colisionais - Magalhães, Willames Ferreira de (2023)
In this thesis we study the interaction of a qubit initially in the pure state interacting with environments constituted by qubits in thermal states, based on collisional quantum models. We initially propose the interaction of the main system with a qubit in the thermal state (environment), where it was possible to perceive the inhabited of the quantum non-Markovianity, which in open quantum systems is associated with cases where information that flowed from the system to the environment eventually returns from the environment to the system. In the study, regular and chaotic behaviors were found from the variations in the transition probabilities of the levels of energy from the system and the environment. Such behaviors are perceived in the dynamics of the entanglement and coherence of the system. Then we add qubits into states thermal effects to the environment and investigated how the interactions of the main system, where we already included entanglement along collisions. The result of this, in addition to the chaotic behavior in the interaction dynamics, was the decrease in the non-Markovianity of the system, where we evaluate this by the trace distance and BLP quantifier, when the environment passes from two to three qubits. The conclusion of the study was that the increase of constituents of the environment implies a transition from non-Markovian to Markovian quantum dynamics, a perception that until then had not been explained under the present viewpoint in the literature.